Meta-Analysis of Low-Intensity versus Standard Anticoagulation for Mechanical Aortic Valves - Naito, Noritsugu; Takagi, Hisato (International Journal of Angiology, 2025)
This meta-analysis aimed to evaluate the long-term outcomes of a low-intensity anticoagulation (LA) strategy in patients undergoing mechanical aortic valve replacement.A systematic search of the databases was conducted through October 2024. Single-arm meta-analysis was performed to estimate the pooled late outcomes associated with LA. The Kaplan–Meier survival curve was reconstructed using individual patient data from included studies to assess overall survival. A standard meta-analysis was then conducted to compare outcomes between LA and standard anticoagulation (SA).Eight studies, comprising 2,426 patients and 21,062.7 patient-years, were included. Five studies involved comparable groups, while three were single-arm studies. The pooled valve-related mortality rate with LA was 0.05 per 100 patient-year, with incidences of prosthetic valve thrombosis, composite of bleeding and thromboembolism, bleeding, and thromboembolism being 0.03, 1.5, 0.93, and 0.46 per 100 patient-year, respectively. The Kaplan–Meier analysis showed overall survival rates at 10 years of 88.5%. Compared with SA, LA was associated with significantly lower risks of all-cause mortality (hazard ratio [HR]: 0.50; 95% confidence interval [CI]: 0.37–0.68; p < 0.01), composite outcome (HR: 0.49; 95% CI: 0.37–0.66; p < 0.01), and bleeding (HR: 0.37; 95% CI: 0.26–0.52; p < 0.01). There were no significant differences in valve thrombosis (HR: 0.52; 95% CI: 0.13–2.11; p = 0.36) or thromboembolic event rates (HR: 0.88; 95% CI: 0.50–1.54; p = 0.65).This meta-analysis suggests that LA is associated with reduced risks of all-cause mortality and bleeding compared with SA, while thromboembolic risks remain comparable.
Keywords: meta-analysis; anticoagulation; mechanical aortic valve replacement